Gender inequality in Latin America and the Caribbean - Inés Berniell; Raquel Fernández; Sonya Krutikova (Inter-American Development Bank (IDB), 2023)
This chapter examines gender inequality, focusing on two critical spheres in which gender inequality is generated: education and work. The objective is to provide a current snapshot of gender inequality across key indicators as well as a dynamic perspective that highlights successes and failures. Facilitating a cross-country comparison as well by grouping countries within Latin America by their level of economics development and drawing comparisons with countries outside the region. Finally, it reflect on differences in the ways that gender inequalities play out across different socio-economic groups, particularly those that highlight other sources of inequality. The second part of the chapter focuses on the worksphere. Here it document significant improvements in female labor force participation over the last 20 years, especially among the least-educated women (those with incomplete secondary education). However, progress has not been equal across all the countries in the region the pace of improvement in this dimension has been slowest in the least economically developed countries. These are also the countries where a significant proportion of the adult working population, especially among men, continue to hold highly conservative norms about women's participation in work.
Keywords: I24; I25; J16; J24; 330; Education and Inequality; Education and Economic Development; Economics of Gender; Human Capital; Skills; Labor Productivity